The Hidden Dangers of PM2.5: Air Pollution and Its Health Risks for High School Students in Bangkok - Kittiwattanokhun, Thanirath; Punyapru, Chatcha; Punyapru, Phitchaya; Jiracheeveewong, Apichaya; Wongsamut, Tiwaruangchay; Saenjaiwut, Wasu; Ekvitayavetchanukul, Pongkit (Journal of Neonatal Surgery, 2025)
Fine particulate matter (PM2.5) pollution is a critical public health concern, particularly in urban centers like Bangkok, where air quality variability poses serious health threats to adolescents. This study examines the effects of PM2.5 exposure on respiratory health among 215 high school students aged 10–18, focusing on symptom severity, medical visits, and risk perception. Findings reveal that 27.9% of students reported severe respiratory symptoms, with an average of 2.48 medical visits per month. Notably, while outdoor exposure demonstrated a weak negative correlation with symptom severity (r = -0.10), the high prevalence of respiratory distress underscores the substantial health burden associated with air pollution. These results highlight the urgent need for evidence-based public health interventions, enhanced air quality monitoring, and stronger policy measures to safeguard adolescent health against environmental pollutants